1995
DOI: 10.3109/17453679508995590
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-free radicals impair fracture healing in rats

Abstract: We studied the effect of oxygen-free radicals on fracture healing. 30 male rats were divided into 2 groups: 15 rats were given saline 5 mL/kg i.p. (control group) and 15 were given zymosan 100 mg/kg i.p. to induce oxygen-free radicals through stimulation of NADPH oxidase in polymorphonuclear leucocytes. 1 hour later, the right forelimbs of the rats were broken by light manual compression. These treatments were given once a day until the fifth post-fracture day. All rats were killed on day 22, and histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 12 publications
3
71
1
6
Order By: Relevance
“…As in some other clinical trials (Prasad et al 2003), the levels of NO were found to be high especially on the postfracture 7th and 14th days in the present study. These fi ndings show that NO production increases in an signifi cant amount in the 2nd and 3rd weeks of fracture, when the most intense oxidative stress occurs (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The extreme production of NO may cause peroxynitrite-related tissue damage and a consequent disturbance of fracture healing, especially at the 2nd and 3rd weeks following the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in some other clinical trials (Prasad et al 2003), the levels of NO were found to be high especially on the postfracture 7th and 14th days in the present study. These fi ndings show that NO production increases in an signifi cant amount in the 2nd and 3rd weeks of fracture, when the most intense oxidative stress occurs (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The extreme production of NO may cause peroxynitrite-related tissue damage and a consequent disturbance of fracture healing, especially at the 2nd and 3rd weeks following the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion mechanisms may cause an oxidative stress injury in a fractured extremity. Some studies indicate that oxidative stress occurred especially on the 7th and 14th days after the fracture (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The common idea in those studies is as follows: the fi rst few days of fracture healing is the ischemia period and no oxidative stress injury occurs during this time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported 30 that negative effects of free oxygen radicals seem to be more prominent during the early phases of the healing period, since antioxidants have been found to be most effective during this phase. In our study, the systemic application of propolis extract after the expansion period was similar to the methods of studies 8 that surveyed bone healing after expansion.…”
Section: Discussionmentioning
confidence: 99%
“…An exaggerated activation of neutrophils using oxygen free radicals is associated with defective healing of bone fracture [106], while an induced neutropenia in animal models of bone defects shows an enhanced osteogenic repair [107]. Likewise, excessive stimulation of macrophages with lipopolysaccharide can decrease their production of BMP-2 causing a delayed bone healing [108].…”
Section: The Uncontrolled Immune Cell Response and Defective Bone Heamentioning
confidence: 99%